Remittances and vulnerability to poverty in rural Mexico - Alejandro de la Fuente (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
International remittances have been portrayed as the human face of globalization given their potential to alleviate poverty by directly increasing household income. Using a panel of rural households in Mexico from October 1998 to November 2000 this study assesses whether this is in fact the case. However, rather than examining whether transfers income would reduce future consumption poverty we asked if transfers are likely to reach people whose conditions are prone to worsen in the future. We used vulnerability to consumption poverty to quantify the extent to which risks and the more permanent disadvantages embedded in most rural livelihoods, can translate into future declines in well-being. We found, contrary to our expectations, a negative and statistically significant relationship between the remittance of transfers, including foreign remittances, and the threat to future poverty that rural households could experience. – globalization ; risk ; vulnerability ; poverty ; private transfers ; Mexico
Keywords: D81; O15; I32; 330; Rücküberweisung (Migranten); Ländliche Armut; Mexiko